An approach to the analysis of foreign policy and security in the Colombia-Ecuador border against drug trafficking - Vélez Tangarife, Álvaro (2011)
This essay describes the international and security policies between Colombia and Ecuador as answers to the formation of a “war economy” in the respective border region. The author argues that the level of conflict in the border area is related to two factors: the activities of both the Colombian army and the insurgent groups, and the increasing weight of both drug trafficking and illegal arms trade in the economy of the region. Both elements are understood from a long term perspective with regard to the armed Colombian conflict in the Northern border region; as well as on the background of the formation of security rhetoric in this region. The fundamental hypothesis of this article is that in order to understand the border dynamics it is necessary to look on the overall evolution of global conflicts related to terrorism and anti-drug warfare.